Antiblocking coating for structural materials

CN118786189BActive Publication Date: 2026-10-23ROHM & HAAS CO
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380024093.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-21
Publication Date
2026-10-23
Estimated Expiration
2043-03-21

AI Technical Summary

Technical Problem

但是薄衬纸和隔离物增加了成本并且产生了额外的固体废物

Benefits of technology

[0031]本发明的方法允许在其表面上具有软的或未固化的涂层的结构组件被堆叠、捆扎或轧制而没有粘连的风险。其使用的固化步骤需要的时间和成本少于完全固化残留的未固化涂层所需的时间和成本。它避免了与防粘连添加剂和薄衬纸相关的成本和问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005014581400000131
    Figure BDA0005014581400000131
  • Figure BDA0005014581400000141
    Figure BDA0005014581400000141
  • Figure BDA0005014581400000142
    Figure BDA0005014581400000142
Patent Text Reader

Abstract

The blocking of coated structural components can be minimized by applying and curing a fast-curing anti-blocking overcoat. Suitable anti-blocking overcoats comprise the following solid components dissolved or suspended in an aqueous solvent: c) a binder in an amount sufficient to form a stable coating; d) 1 to 20 wt.% of a film-forming high Tg polymer having a glass transition temperature of at least 80 °C; e) 1 to 25 wt.% of a hydrophobic additive; and f) optionally up to 70 wt.% of a filler, wherein (1) the solids content of the composition is at least 5 wt.%; (2) the weight percentages listed for each of components (a)-(d) are based on the total weight of the aqueous composition; and (3) the pH of the composition is between 2 and 6.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of coatings for structural components. Background Technology

[0002] Structural components include a wide variety of solid objects, such as beams, slats, sheets, membranes, tubes, and other molded articles, such as door components, window components, fence and deck components, furniture components, and housings of machinery. Depending on their intended use, structural components are made of a variety of structural materials; examples of structural materials include wood, metal, plastic, concrete, fiberglass, and glass.

[0003] The outer surfaces of structural components are often coated with one or more coating materials to improve appearance, protect them from environmental impacts, enhance safety in use, and / or provide other desired properties. Examples of such coatings include various paints, varnishes, shellacs, sealants, and curable powder coatings.

[0004] "Blocking" is a common problem with coated structural components. Many coating compositions feel quick to the touch but take much longer to fully cure, sometimes even days. Other coating compositions are intentionally soft even after full curing. Individual structural components can be stacked or bundled after they leave the production line, so that their weight presses their surfaces together. Or sheets or films can be rolled up after they leave the production line, so that the surface of one layer from the roll is pressed against the surface of another layer from the same roll. Time and pressure cause the still-soft coating to adhere to the two surfaces that are pressed between them, resulting in the coating bonding the two surfaces together, thus forming a solid block of structural components or layers intended to be separated. Separating these surfaces can damage the surface or the coating, or both.

[0005] For clarity, it should be noted that the “curing” of a coating composition can occur through two separate mechanisms: physical drying and chemical curing. See, for example, Muller et al. Coatings Formulation, 2nd Edition Vincentz Network GmbH & Co. (2011), Chapter 1.1.1 (Solidification of Paints). In physical drying, the surface cures by evaporating the solvent, making the surface feel dry to the touch and adhere to the surface to which it is applied. In chemical curing, the chemical reaction between molecules in the coating and molecules on the surface further solidifies the cohesiveness of the coating and its adhesion to the surface. The curing of a coating composition may involve one or both of these mechanisms. For many coatings, physical drying occurs faster than chemical curing, causing structural components to feel dry and be stacked, bundled, or rolled up before chemical curing is complete; this provides common conditions for adhesive formation.

[0006] Adhesion and methods to avoid adhesion are discussed in coating industry references such as: “Blocking Resistance in Coatings: Composition Factors to Consider”, https: / / www.lubrizol.com / Coatings / Blog / 2019 / 11 / Blocking-Resistance; “Fluoroadditives: Antiblock Characteristics in Architectural Paint Systems”, Paint and Coatings Industry Magazine, https: / / www.pcimag.com / articles / 83026-fluoroadditives-antiblock-characteristics-in-architectural-paint-systems; and “EBook A Guide to Applying Powder Coatings”, www.ifscoatings.com.

[0007] Sometimes, adhesion can be reduced by performing longer curing cycles on the structural components to more fully cure the coating composition, but this takes longer and requires additional investment in facilities and equipment to keep each structural component separate from the others until the coating composition is fully cured. Alternatively, anti-adhesion additives can be added to the coating composition, but these increase costs and may interfere with the coating's adhesion to the surface it is applied to. Another option is to place thin liner paper or spacers between the surfaces of the different structural components to keep them separate until they are fully cured, as is common in customer-assembled furniture boxes. However, liner paper and spacers increase costs and generate additional solid waste.

[0008] The goal is to find a fast, inexpensive, and low-solid-waste method to reduce the adhesion of structural components. Summary of the Invention

[0009] One aspect of the present invention is a method for preventing structural components from sticking together, the method comprising the following steps:

[0010] 1) Provide a structural component including at least one surface (“adhesion-forming surface”) coated with a primary coating composition that facilitates adhesion;

[0011] 2) Apply an anti-adhesion outer coating composition to the adhesion-forming surface, the anti-adhesion outer coating composition containing...

[0012] a) Solvent;

[0013] b) Adhesive, and

[0014] c) Film-forming high Tg polymers, which have glass transition temperatures above 80°C; and

[0015] 3) Curing the anti-stick coating composition under conditions suitable for forming a non-sticking anti-adhesion coating.

[0016] The phrase “easy to adhere” in relation to the composition means that the composition will adhere to a surface other than the adhesion-forming surface, which is pressed against the adhesion-forming surface at a temperature of up to 50°C for at least one hour.

[0017] A second aspect of the invention is an aqueous composition that can be used as an anti-adhesion outer coating composition and comprises the following solid components dissolved or suspended in an aqueous solvent:

[0018] a) An adhesive, in sufficient quantity to form a stable coating;

[0019] b) 1% to 20% by weight of film-forming high Tg polymers with a glass transition temperature of at least 80°C;

[0020] c) 1% to 25% by weight of hydrophobic additives; and

[0021] d) Optionally up to 70% by weight of filler,

[0022] Wherein (1) the solids content of the composition is at least 5% by weight; and (2) the weight percentages listed for each of components (a)-(d) are based on the total weight of the aqueous composition containing the solvent.

[0023] Furthermore, (3) the pH of the aqueous composition is between 2 and 6. The term "solid" in this specification refers to a component that is a solid or waxy solid at 25°C when suspended in a solvent. Components (a)-(d) are solids.

[0024] A third aspect of the invention is a structural member comprising at least one surface coated with:

[0025] a. at least one layer of a primary coating composition; and

[0026] b. A layer of at least one anti-adhesion outer coating on top of the primary coating composition, the anti-adhesion outer coating comprising:

[0027] i. An adhesive, in sufficient quantity to form a stable coating;

[0028] ii. 1% to 20% by weight of film-forming high Tg polymers with a glass transition temperature of at least 80°C;

[0029] iii. 1% to 25% by weight of hydrophobic additives; and

[0030] iv. Optionally up to 70% by weight of filler.

[0031] The method of this invention allows structural components with soft or uncured coatings on their surfaces to be stacked, bundled, or rolled without the risk of sticking. The curing step required is less time-consuming and costly than the time-consuming and costly process required to fully cure any remaining uncured coating. It avoids the costs and problems associated with anti-sticking additives and thin linerboard. Detailed Implementation

[0032] The method of the present invention uses an anti-adhesion outer coating to prevent structural components from sticking together during storage and transportation.

[0033] Structural components are discussed in the background section. Examples of structural components include beams, plates, studs, tenons, cylinders, tubes, sheets, membranes, and other molded articles. Examples of molded articles include door components, window components, fence and deck components, stair components, furniture components, decorative moldings, and housings of machinery.

[0034] Structural components may optionally include wood, metal, polymer, concrete, fiberglass, or glass. In some embodiments, the structural component includes wood, and in some of those embodiments, the structural component is in the form of beams, slabs, sheets, studs, tenons, or parts for doors, windows, or furniture. In some embodiments, the structural component includes polymer, metal, or fiberglass, and in some of those embodiments, the structural component is a rolled sheet or membrane.

[0035] All solid objects, including structural components, inherently have surfaces. In this invention, at least one surface of the structural component (referred to as the "adhesion-forming surface") includes a primary coating composition applied thereto. The primary coating composition readily adheres after step (a). "Frequently adheres" means that if the adhesion-forming surface and another surface are pressed together at a temperature up to 50°C for at least one hour, the primary coating composition will adhere to the surface (other than the adhesion-forming surface). In some cases, adhesion can be achieved by pressing another surface against the adhesion-forming surface at a temperature of 25°C or 50°C with a pressure of 1 psi, 2 psi, or 4 psi for 1, 2, 4, 8, or 24 hours or at least one week.

[0036] Because the primary coating composition is not fully cured, it may be prone to sticking. In some embodiments, full curing of the primary coating composition (making it less prone to sticking) requires standing at ambient temperature for at least 2 hours, or at least 6 hours, or at least 24 hours, or at least 72 hours, or at least one week.

[0037] Alternatively, the primary coating composition may be prone to adhesion because it has a low glass transition temperature, making it easy to stick even when fully cured. For example, the primary coating composition may have a glass transition temperature below 50°C, or not exceeding 40°C, or not exceeding 30°C, or not exceeding 25°C, or not exceeding 20°C, or not exceeding 10°C, or not exceeding 0°C.

[0038] In some embodiments, the primary coating composition is a paint, varnish, shellac, sealant, or weather-resistant coating. In some embodiments, the primary coating composition, upon complete curing, is decorative and optionally contains pigments or metallic flakes. In some embodiments, the primary coating composition is a clear coating. In some embodiments, the primary coating composition, upon complete curing, is waterproof or weather-resistant. In some embodiments, the primary coating, upon complete curing, is abrasion-resistant or scratch-resistant. In some embodiments, upon complete curing, the primary coating is acid-resistant or resistant to other chemicals.

[0039] Primary coating compositions and their components are known and commercially available. In many embodiments, paints comprise solvents, binders, and pigments. In many embodiments, varnishes comprise solvents, resins, drying oils, and driers. In many embodiments, insecticides comprise resins and solvents, optionally containing pigments. In many embodiments, weather-resistant coatings contain hydrophobic polymers dissolved or emulsified in solvents. In some embodiments, the solvent used in the primary coating composition is organic, and in some embodiments, the solvent is aqueous. Primary coating compositions may also contain polymers, additives, and fillers to provide improved weather resistance or other properties. Common additives and their uses are described in J. Bieleman (ed.), Additives for Coatings, Wiley-VCH Verlag GmbH (2000).

[0040] To prevent adhesion, an anti-adhesion outer coating composition is applied to the adhesion-forming surface on top of a partially or fully cured primary coating composition. The anti-adhesion outer coating composition comprises a solvent, a binder, and a film-forming high Tg polymer with a glass transition temperature (Tg) above 80°C.

[0041] The purpose of the solvent is to dissolve the binder and high-Tg polymer or to hold them in a suspension or emulsion to facilitate the application of them to the adhesion-forming surface. The solvent is essentially removed from the adhesion-forming surface during the curing step. For clarity, the term "solvent" does not mean that all components of the anti-adhesion coating composition are soluble in that solvent. Some or all components of the anti-adhesion coating composition may be insoluble and held in a suspension or emulsion in the solvent.

[0042] Solvents used for coatings are well known. In some embodiments, the solvent is an organic solvent, such as acetone, pentane, hexane, toluene, xylene, solvent oil, methyl ethyl ketone; n-butyl acetate, ethylene glycol, or lower alcohols such as propanol or butanol. In some embodiments, the solvent is aqueous. Aqueous solvents can be substantially neutral (pH 6 to 8), acidic (pH 2 to 6), or basic (pH 8 to 12). In some embodiments, the solvent is an acidic aqueous solvent. In some embodiments, organic solvents may have the advantage of dissolving more components of the anti-blocking outer coating composition and / or drying faster, but aqueous solvents may have the advantage of reducing the emission of volatile organic compounds from the anti-blocking outer coating composition. Solvents are generally commercially available from a variety of sources.

[0043] The purpose of an adhesive is to form a film on an adhesive-forming surface and, after a curing step, retain the solid components of the anti-blocking overcoating composition on the adhesive-forming surface. Adhesives used for coatings are well known. Examples of commonly used adhesives include acrylic polymers, alkyd polymers, polyurethane polymers, epoxy polymers, polyester polymers, and phenolic resins. Examples of other known adhesives include certain natural resins and starches, styrene-butadiene polymers, and silanes. Examples are described in publications such as U.S. Patent 6,660,788B2, European Patent Publication EP 0 819 744 A2, German Patent Publication DE 3,123,598A1, and “Paints” published by the Department of Chemistry, University of York at https: / / www.essentialchemicalindustry.org / materials-and-applications / paints.html (March 18, 2013).

[0044] In some embodiments, the adhesive comprises an acrylic polymer. An acrylic polymer is a polymer or copolymer containing repeating units derived from an acrylic monomer. Acrylic monomers include acrylic acid, methacrylic acid, and their esters. Exemplary esters used in acrylic monomers include alkyl esters, such as alkyl groups containing 1-8 carbon atoms or 1-4 carbon atoms, or in some cases, methyl or ethyl groups. Particularly useful acrylic monomers are acrylic acid, methacrylic acid, butyl acrylate, 2-ethylhexyl acrylate, methyl acrylate, ethyl acrylate, methyl methacrylate, and ethyl methacrylate.

[0045] Exemplary acrylic polymers may contain at least 70%, or at least 80%, or at least 90%, or at least 95% repeating units derived from acrylic monomers. Exemplary acrylic polymers may contain up to 100% repeating units derived from acrylic monomers. Some exemplary acrylic polymers are copolymers containing units derived from two or more acrylic monomers, such as copolymers of butyl acrylate with methyl methacrylate and / or methacrylic acid. Some exemplary acrylic polymers may also contain repeating units derived from non-acrylate-bonded unsaturated comonomers, such as ethylene, propylene, butene, or styrene.

[0046] The selection of acrylic monomers and their proportions depends on the intended use of the acrylic polymer. Adhesives typically have a glass transition temperature (Tg) of at least -45°C and at most +65°C. Adhesives that will experience large thermal expansion at low temperatures, such as outdoor coatings in cold climates, can be selected to have a low Tg, such as at most -15°C, or -20°C, or -30°C. Adhesives that will experience little thermal expansion, such as indoor coatings, can have a higher Tg, such as at least 0°C or at least 10°C. It is known that increasing the content of certain monomers, such as methyl methacrylate, increases the Tg of the resulting polymer, and it is known that increasing the content of other monomers, such as butyl acrylate, decreases the Tg of the resulting polymer.

[0047] Adhesives must form a film under the conditions under which they are applied to the intended substrate. "Film formation" refers to the ability of a substance to form a film when applied to a solid surface. The ability of polymers and their solutions or emulsions to form films is known and described in publications such as: PASteward et al., "An Overview of Polymer Latex Film Formation and Properties", 86 Advances in Colloid and Interface Science, 195-267 (2000); and J. Guerts et al., "New Waterborne Acrylic Binders for Zero VOC Paints", 5 J. Coating Technol. Res., 57-63 (2008). Generally, the film-forming ability of polymers increases with lower molecular weight and / or lower Tg, and decreases with higher molecular weight and / or higher Tg. Binders with a Tg above 25°C may require additives to help them form films, while polymers with a lower Tg are generally easier to form films.

[0048] In some embodiments, a monomer mixture is selected such that the binder is water-soluble. In other embodiments, the binder is insoluble in water but is held in suspension using an emulsifier. The emulsifier keeps the insoluble elements suspended in an aqueous solvent. Emulsifiers are typically surfactants, such as anionic and nonionic surfactants. For example, some commonly used emulsifiers are fatty alkyl sulfates (such as sodium lauryl sulfate), alcohol ether sulfates, aryl sulfonates (such as branched dodecylbenzene sulfonate), alkyl diphenyl ether disulfonates (such as disodium lauryl phenyl ether disulfonate), nonylphenol ether sulfates (such as ammonium nonylphenol ether sulfate), fatty alcohol ethoxylates, nonylphenol ethoxylates, or alkyl phosphates (such as ammonium phosphate), polyoxyethylene tridecyl ether. Suitable emulsifiers are available under the trademark DOWSIL. TM TERGITOL TM TRITON TM RHODAFAC TM RHODACAL TM 、DISPONIL TM LUTENSOL TM and DOWFAX TM .

[0049] Examples of commercially available adhesives include RHOPLEX. TM ParaloidTM and MAINCOTE TM The trademarks are derived from acrylic polymers and polymer emulsions from Dow Chemical Company.

[0050] The purpose of film-forming high Tg polymers is to add solid components to an anti-blocking outer coating that do not soften at room temperatures where the structural components may be stored or transported. Suitable high Tg polymers are known and commercially available. Examples of high Tg polymers include certain acrylics, polystyrene, polyurethanes, poly(vinyl alcohol), vinyl acetate, vinyl acrylate, styrene acrylate, and styrene butadiene polymers. In some embodiments, the high Tg polymer has a glass transition temperature (Tg) of at least 85°C, or at least 90°C, or at least 95°C, or at least 100°C. High Tg polymers do not have a maximum Tg, but Tgs above 200°C or 150°C are generally not required.

[0051] High-Tg polymers must be film-forming. Generally, the film-forming ability of a polymer increases with lower molecular weight and / or lower Tg, and decreases with higher molecular weight and / or higher Tg. In some embodiments, additives may be added to the high-Tg polymer to improve its film-forming ability. In some embodiments, the molecular weight of the high-Tg polymer may be kept low to improve its film-forming ability.

[0052] In some embodiments, the high Tg film-forming polymer is water-soluble or water-swellable under selected conditions. It is not desirable to be constrained to assume that the interaction of water-soluble or water-swellable polymers with water can impart increased flexibility to higher molecular weight and higher Tg polymers, which enhances their film-forming ability. Some acrylic polymers can be suspended in emulsions under acidic conditions but are water-soluble or water-swellable under neutral or alkaline conditions. Aqueous emulsions of such water-soluble or water-swellable film-forming high Tg polymers are commercially available, for example, from ACRYSOL. TM The ASE trademark was acquired from Dow Chemical Company.

[0053] In some embodiments, the anti-blocking outer coating composition further comprises one or more hydrophobic additives. One purpose of the hydrophobic additives is to improve the water repellency of the anti-blocking outer coating, which minimizes the risk of softening upon continuous exposure to moisture or high humidity. Hydrophobic additives for coatings are known and commercially available. Hydrophobic additives include various waxes (e.g., paraffin wax and high-melting-point waxes); organosilanes, siloxanes, and silicones (e.g., octyltriethoxysilane and polydimethylsiloxane); and hydrophobic polymers (e.g., polyethylene, polypropylene, and polytetrafluoroethylene). In some embodiments, the hydrophobic additives have a melting temperature of at least 60°C, or at least 70°C, or at least 80°C, or at least 85°C, or at least 90°C. A maximum melting temperature for the hydrophobic additive is not required, but melting points above 200°C or 150°C are generally not necessary. In aqueous anti-blocking outer coating compositions, emulsifiers as previously described can be used to suspend the hydrophobic additives in the composition. The production of emulsified hydrophobic additives is described in publications such as U.S. Patent 3,096,232 and U.S. Patent 6,033,736. Examples of suitable hydrophobic additives are available commercially available under the trademark DOWSIL. TM (Dow Chemical Company), Michem Dispersion (Michelman), Lubronil and Wükonil (Münzing), and Aquacer (BYK).

[0054] In some embodiments, the anti-blocking outer coating composition further comprises one or more fillers. Fillers are solid particles added to the coating to improve properties and / or reduce costs. In the compositions of the present invention, it is assumed, but not intended to be limiting, that fillers can contribute to creating a non-uniform surface texture in the anti-blocking outer coating, which helps prevent the outer coating from sticking. Suitable fillers for coatings are known and commercially available. Examples of suitable fillers include clays (such as kaolin, diatomaceous earth, glass powder, and microspheres), aluminum hydroxide, and various powdered minerals (such as calcium carbonate, dolomite, feldspar, mica, quartz, silica, and silicates), talc, and metal carbonates. Other examples of suitable fillers include common mineral pigments such as titanium dioxide and carbon black. Fillers, their production, and uses are described in publications such as: Gysau, Fillers for Paints (3rd edition), Vincentz Network GmbH & Co. (2017); and “Functional Silicate Fillers: Basic Principles”, Painting & Coatings Industry (August 1, 2002) (https: / / www.pcimag.com / articles / 84909-functional-silicate-fillers-basic-principles).

[0055] In some embodiments, the filler is a high surface area material. Surface area is typically measured based on oil absorption value, as described in ASTM D281 (Standard Test Method for Oil Absorption of Pigments by Spatula Rub-Out). In some embodiments, the filler used in this invention may have an oil absorption value of at least 25 g / 100 g, or at least 30 g / 100 g, or at least 40 g / 100 g, or at least 50 g / 100 g. There is no maximum surface area, but an oil absorption value higher than 250 g / 100 g may be unnecessary.

[0056] Some commonly used fillers are insoluble and can be suspended in the anti-blocking coating composition using emulsifiers.

[0057] Examples of suitable fillers are available commercially from the following brands: ASP (BASF), Minex and Imsil (Covia), Zoco (American Zinc Recycling), Opacilite and DiaFil and Mica MU (Imerys), Lo-Vel (PPG), and Hakuenka and Omyawhite (Omya).

[0058] As previously described, the binder, high Tg polymer, hydrophobic additive, and filler are the solids in the anti-blocking top coating composition. In some embodiments, it is advantageous to maximize the solids in the anti-blocking top coating composition to reduce drying time and minimize the release of volatile organic solvents from the composition during drying. In some embodiments, the solids content of the anti-blocking top coating composition, based on the total weight of the composition, is at least 5% by weight, or at least 10% by weight, or at least 15% by weight, or at least 20% by weight, or at least 24% by weight. There is no maximum solids content, as long as the anti-blocking top coating composition can be applied smoothly and easily. In some embodiments, the solids content of the aqueous composition, based on the total weight of the composition, is at most 70% by weight, or at most 50% by weight, or at most 40% by weight, or at most 33% by weight.

[0059] The amount of binder should be sufficient to form a stable coating, meaning that the solid components of the composition adhere firmly to the film-forming surface. In some embodiments of the anti-adhesion outer coating composition, the binder accounts for at least 0.25% by weight, or at least 0.5% by weight, or at least 1% by weight, or at least 1.2% by weight of the composition (including solvent). In some embodiments of the anti-adhesion outer coating composition, the binder accounts for at most 25% by weight, or at most 20% by weight, or at most 10% by weight, or at most 5% by weight, or at most 3% by weight of the composition (including solvent). In some embodiments of the anti-adhesion outer coating composition, the binder accounts for at least 1% by weight, or at least 2% by weight, or at least 3% by weight, or at least 5% by weight of the solids (excluding solvent). In some embodiments of the anti-adhesion outer coating composition, the binder accounts for at most 50% by weight, or at most 20% by weight, or at most 10% by weight of the solids (excluding solvent).

[0060] In some embodiments of the anti-blocking outer coating composition, the film-forming high Tg polymer accounts for at least 1% by weight, or at least 2% by weight, or at least 3% by weight, or at least 5% by weight of the composition (including solvent). In some embodiments of the anti-blocking outer coating composition, the film-forming high Tg polymer accounts for at most 20% by weight, or at most 15% by weight, or at most 10% by weight of the composition (including solvent). In some embodiments of the anti-blocking outer coating composition, the film-forming high Tg polymer accounts for at least 2% by weight, or at least 4% by weight, or at least 6% by weight, or at least 10% by weight of the solid content (excluding solvent). In some embodiments of the anti-blocking outer coating composition, the high Tg polymer accounts for at most 50% by weight, or at most 40% by weight, or at most 30% by weight of the solid content (excluding solvent).

[0061] In some embodiments of the anti-adhesion coating composition, the hydrophobic additive comprises at least 1% by weight, or at least 2% by weight, or at least 3% by weight of the composition (including solvent). In some embodiments of the anti-adhesion coating composition, the hydrophobic additive comprises at most 20% by weight, or at most 15% by weight, or at most 10% by weight of the composition (including solvent). In some embodiments of the anti-adhesion coating composition, the hydrophobic additive comprises at least 2% by weight, or at least 5% by weight, or at least 10% by weight of the solid content (excluding solvent). In some embodiments of the anti-adhesion coating composition, the hydrophobic additive comprises at most 40% by weight, or at most 30% by weight, or at most 20% by weight of the solid content (excluding solvent).

[0062] In some embodiments of the anti-blocking outer coating composition, the filler comprises at least 5% by weight, or at least 8% by weight, or at least 10% by weight, or at least 12% by weight of the composition (including solvent). In some embodiments of the anti-blocking outer coating composition, the filler comprises at most 50% by weight, or at most 30% by weight, or at most 20% by weight of the composition (including solvent). In some embodiments of the anti-blocking outer coating composition, the filler comprises at least 5% by weight, or at least 10% by weight, or at least 20% by weight, or at least 30% by weight, or at least 40% by weight of the solids content (excluding solvent). In some embodiments of the anti-blocking outer coating composition, the filler comprises at most 70% by weight or at most 60% by weight of the solids content (excluding solvent).

[0063] Optionally, the anti-blocking outer coating composition may also contain other additives, such as thickeners, defoamers, surfactants, stabilizers, wetting agents, leveling agents and coalescing agents, antioxidants and biocides. Common additives and their uses are described in J. Bieleman (ed.), Additives for Coatings, Wiley-VCH Verlag GmbH (2000). In some embodiments, the other additives constitute no more than 5% by weight, or no more than 3% by weight, or no more than 2% by weight, or no more than 1% by weight of the aqueous composition (including solvents). In some embodiments, the other additives constitute no more than 10% by weight, or no more than 5% by weight, or no more than 2% by weight of the solids in the aqueous composition.

[0064] In the method of the present invention, it is advantageous to select the components of the anti-adhesion outer coating composition such that the anti-adhesion outer coating composition cures to a degree that it is not easily adhered to quickly under the conditions of the curing step. The faster curing rate of the anti-adhesion outer coating composition allows structural components to be stacked, bundled, or rolled up without requiring time to fully cure the primary coating composition. In some embodiments, the components of the anti-adhesion outer coating composition are selected such that the anti-adhesion outer coating composition is not easily adhered to after curing for no more than 1 hour, or no more than 30 minutes, or no more than 15 minutes, or no more than 5 minutes, or no more than 2 minutes, or no more than 1 minute under the conditions of the curing step.

[0065] The aqueous anti-adhesion coating composition, which is particularly useful in the method of the present invention, comprises the following solid components dissolved or suspended in an aqueous solvent:

[0066] a) 1% to 10% by weight of adhesive;

[0067] b) 1% to 20% by weight of film-forming high Tg polymers with a glass transition temperature of at least 80°C;

[0068] c) 1% to 25% by weight of hydrophobic additives; and

[0069] d) Optionally up to 70% by weight of filler,

[0070] Wherein (1) the solids content of the composition is at least 5% by weight; and (2) the weight percentages listed for each of components (a)-(d) are based on the total weight of solids in the aqueous composition; and

[0071] (3) The pH of the aqueous composition is between 2 and 6.

[0072] The adhesive has the description, exemplary embodiments, and exemplary concentrations previously described. In some embodiments, the adhesive is an acrylic polymer with a Tg not exceeding 25°C.

[0073] The film-forming high Tg polymer has the description, exemplary embodiments, and exemplary concentrations previously described. In some embodiments, the film-forming high Tg polymer is an acrylic polymer, and in some embodiments, the acrylic polymer is emulsified in an acidic solution and is water-soluble or water-swellable in a neutral or alkaline solution.

[0074] The hydrophobic additives and fillers are as described previously, with exemplary embodiments and exemplary concentrations. Aqueous compositions may also contain other additives as previously described.

[0075] In some embodiments, the aqueous composition has a pH of at least 4 or at least 5. In some embodiments, the aqueous composition has a pH of at most 7 or at most 6.

[0076] In the method of the present invention, an anti-adhesion outer coating composition is applied to the adhesion-forming surface. Known application methods can be used, such as spraying, brushing, roller coating, curtain coating, or dip coating. In some embodiments, the anti-adhesion outer coating composition is sprayed onto the adhesion-forming surface.

[0077] After being applied to the adhesion-forming surface, the anti-adhesion outer coating composition undergoes a curing step until it is no longer easily adhered (as previously defined). In some embodiments, the curing temperature is at least 20°C, or at least 35°C, or at least 50°C, or at least 75°C, or at least 100°C. In some embodiments, the curing temperature is at most 300°C, at most 250°C, or at most 225°C, or at most 200°C, or at most 160°C. In some embodiments, curing is accompanied by an airflow to remove solvent from the anti-adhesion composition. In some embodiments, curing is carried out in an air atmosphere; in some embodiments, curing is carried out in an inert atmosphere such as nitrogen. In some embodiments, the curing step is completed within a time not exceeding 1 hour, or not exceeding 30 minutes, or not exceeding 15 minutes, or not exceeding 5 minutes, or not exceeding 2 minutes, or not exceeding 1 minute.

[0078] After the curing step, the adhesion-forming surface of the structural component contains a layer of at least one primary coating composition, covered with at least one anti-adhesion outer coating layer. Areas of the primary coating composition may be prone to adhesion, except that the cured anti-adhesion outer coating prevents the primary coating composition from contacting surfaces other than the adhesion-forming surface and thus prevents adhesion. In some embodiments, the adhesion-forming surface (with the anti-adhesion outer coating) can be pressed against another surface for at least 1 hour, at least 6 hours, or at least 24 hours without substantially any adhesion. In some embodiments, the temperature during this pressure process can be up to 50°C. In some embodiments, the pressure can be up to 1 psi, or at least 2 psi, or at least 3 psi. In some embodiments, the relative humidity can be up to 50%, or 57%, or 90%, or 100%.

[0079] The content of the dried anti-blocking outer coating reflects the solids content of the applied and cured anti-blocking outer coating composition, having the same exemplary components and concentrations. In some embodiments, the cured anti-blocking outer coating contains no more than 5% by weight, or no more than 3% by weight, or no more than 1% by weight, or no more than 0.5% by weight of solvent. The desired amount of solvent is not present in the outer coating, but in some cases, removing the solvent to a content below 0.1% by weight may be impractical. The anti-blocking outer coating does not necessarily have a certain thickness, but in some embodiments, the average thickness of the outer coating is at least 5 μm, or at least 10 μm, or at least 25 μm, and in some embodiments, the average thickness is at most 600 μm, or at most 500 μm, or at most 300 μm.

[0080] Unlike many outer coatings used on structural components, the anti-stick outer coating of this invention does not require high weather resistance or abrasion resistance. The anti-stick outer coating simply needs to remain in place until the primary coating composition is fully cured and no longer forms clumps. In many cases, the primary coating composition is fully cured within days or weeks after the curing step is completed. In many cases, the primary coating composition is fully cured before the structural component is received by the user and put into use. In many embodiments, the anti-stick outer coating is no longer needed after the structural component is put into use. The anti-stick outer coating may be allowed to wear or weather over time, like floor wax or polish. In some embodiments, this difference in use may influence the choice of additives in the anti-stick outer coating composition. Additives providing antioxidant, lightfastness, scratch resistance, abrasion resistance, and weather resistance may be unimportant and can be excluded from the anti-stick outer coating composition. An anti-stick outer coating that is intended to wear or weather during normal use may be referred to as a sacrificial outer coating.

[0081] In some embodiments, after 6 months of normal use, at least 25% by weight, or at least 50% by weight, or at least 75% by weight of the outer coating has worn away from the structural component. In other embodiments, the structural component is used for shielding purposes, such as within a wall, and substantially no outer coating has been worn away.

[0082] Example

[0083] The invention is further illustrated by the following examples, which are illustrative and not limiting. Comparative examples are included to demonstrate the beneficial effects of some components of the invention.

[0084] Substrate preparation

[0085] Prepare a slow-curing primary coating composition. Prepare an aqueous suspension of the pigment by blending the materials listed in Table 1A until a suspension is formed.

[0086]

[0087]

[0088] After the suspension has formed, reduce the shear force in the mixture and add the materials listed in Table 1B in the order listed. Continue mixing for another hour or until smooth.

[0089]

[0090] 1. The polymer emulsion contains a random copolymer of 86% butyl acrylate, 12.3% methyl methacrylate and 1.7% methacrylic acid, with a Tg of -35℃ and a concentration of 55% solids.

[0091] The total materials in Tables 1A and 1B are 100% by weight. The resulting primary coating composition contains 41% by volume and 56% by weight solids. A 100mm wide GARDCO... TM A multi-gap square applicator (Paul N. Gardner Company, Inc.) was used to apply the primary coating composition to an aluminum Q panel (A412 ground finish, Q Labs Corporation) to cast a 381-micron thick wet film onto the substrate. Each coated panel was dried under ambient conditions for 7 days (21°C and 50% RH).

[0092] External coating composition and application :

[0093] Add the amounts of water shown in Table 2 to the container, then add the other ingredients shown in Table 2 in the order and amounts shown in Table 2 to the container and mix until homogeneous. All amounts shown are parts by weight. Test the pH of each outer coating composition.

[0094] Use 50mm wide GARDCO TM A multi-gap square applicator (Paul N. Gardner Corporation) applies each topcoat composition to several of the previously described substrates to cast a 76-micron-thick wet film onto the substrates. Some of the topcoat substrates are dried for 1 to 3 days under ambient conditions (approximately 21°C and approximately 50% relative humidity). The other topcoat substrates are dried for 24 hours in an oven at 50°C and approximately 30% relative humidity, followed by equilibration under ambient conditions for 1–7 days.

[0095] test

[0096] Ambient temperature adhesion Aluminum Q panels (A612 mill-finished, Q Labs) were cut into 5.12cm × 5.12cm (2in × 2in) squares, and the cut squares were placed directly on top of a 5.12cm × 5.12cm (2in × 2in) square of an outer-coated panel cured at ambient temperature. Each stack of panels was subjected to a pressure of 10 psi. The pressure was maintained for 4 hours, then removed. After 1 minute, the Q panels were removed to determine anti-stick properties. The nature of the coating damage and the amount of coating removed were recorded. If the Q panels were easily removed, the coating was acceptable. If removing the Q panels required effort or damaged the primary coating or the anti-stick outer coating, the coating was unacceptable. For each coated Q panel, a total of two square coatings were tested under the indicated weight load, and the results were accepted if they were identical (acceptable or unacceptable). The results are shown in Table 2.

[0097] The same test was performed on two square Q panel substrates with a primary coating but no anti-adhesion outer coating. The square without an outer coating also failed.

[0098] High-temperature adhesion The aforementioned tests were repeated on the oven-cured coated panels, except that the pressurized panels were placed in an oven at 50°C and approximately 30% relative humidity for 4 hours before the tests. The results are shown in Table 2.

[0099]

[0100] Test methods

[0101] Glass transition temperature: ASTM E1356-08 (2014) determines the glass transition temperature by differential scanning calorimetry.

[0102] Oil absorption: ASTM D281 (2021) determines the oil absorption of pigments by wiping with a spatula.

Claims

1. An aqueous composition comprising the following solid components dissolved or suspended in an aqueous solvent: a) An adhesive, in sufficient quantity to form a stable coating; b) Film-forming high Tg polymers with a glass transition temperature (Tg) of at least 80 °C, ranging from 1 wt% to 20 wt%. c) 1% to 25% by weight of hydrophobic additives; and d) Optionally up to 70% by weight of filler, (1) the solids content of the composition is at least 5% by weight; (2) the weight percentages listed for each of components (a)-(d) are based on the total weight of the aqueous composition including the solvent; and (3) the aqueous composition has a pH between 2 and 6.

2. The aqueous composition according to claim 1, wherein the binder comprises an acrylic polymer with a Tg not exceeding 25°C.

3. The aqueous composition according to claim 1, wherein the high Tg polymer comprises an acrylic polymer with a glass transition temperature of at least 90°C.

4. The aqueous composition according to claim 1, wherein the high Tg polymer can form an emulsion in an acidic solution, but is water-soluble or water-swellable in a neutral or alkaline solution.

5. The aqueous composition according to claim 1, wherein the hydrophobic additive comprises wax, silane, or polyolefin polymer.

6. The aqueous composition according to claim 1, wherein the aqueous composition contains at least 8% by weight of filler based on the total weight of the composition.

7. The aqueous composition according to claim 1, wherein, based on the total weight of the composition: a) The adhesive comprises an acrylic polymer with a Tg not exceeding 25°C and accounts for 1% to 10% by weight of the aqueous composition. b) The high Tg polymer comprises an acrylic polymer with a glass transition temperature of at least 90°C and accounts for at least 2% by weight of the aqueous composition. c) The hydrophobic additive comprises wax, silane, or polyolefin polymer, and constitutes at least 2% by weight of the aqueous composition. d) The filler constitutes at least 8% by weight of the aqueous composition. e) The solids content of the aqueous composition is at least 20% by weight.

8. The aqueous composition according to claim 1, wherein the composition is free of antioxidant additives or light stabilizer additives.

9. A method for preventing structural components from sticking together, the method comprising the following steps: a) Provide a structural component including at least one adhesion-forming surface coated with a primary coating composition that facilitates adhesion; b) Apply an anti-adhesion coating composition containing the following components to the adhesion-forming surface: i) Solvent, ii) Adhesives, and iii) A film-forming high Tg polymer, said polymer having a glass transition temperature above 80°C, wherein said anti-blocking outer coating composition has a pH between 2 and 6; and c) Curing the anti-adhesion coating composition under conditions suitable for forming a non-adhesive anti-adhesion outer coating. The phrase "easy to adhere" in relation to the composition means that the composition will adhere to a surface other than the adhesion-forming surface, which is pressed against the adhesion-forming surface at a temperature up to 50°C for at least one hour.

10. A structural member comprising at least one surface coated with the following: a) at least one layer of the primary coating composition; and b) A layer of at least one anti-adhesion outer coating on top of the primary coating composition, the anti-adhesion outer coating comprising: i) 1% to 50% by weight of adhesive; ii) 2% to 50% by weight of film-forming high Tg polymers with a glass transition temperature of at least 80°C; iii) 2% to 40% by weight of hydrophobic additives; and iv) Optionally up to 70% by weight of filler, wherein the anti-adhesion outer coating is formed of a composition having a pH between 2 and 6.

Citation Information

Patent Citations

  • Binders for aqueous coating compositions, process for the preparation thereof, and the use thereof

    DE3123598A1

  • Binder composition and aqueous coating composition

    EP0819744A2

  • Aqueous emulsions of waxes and resins

    US3096232A

  • Aqueous wax emulsion as paint primer and paint repair adhesive

    US6033736A

  • Water borne binder composition

    US6660788B2